Pengaruh Penggunaan Media Balok Cuisenaire terhadap Kemampuan Berhitung Permulaan Anak Usia Dini Kelompok B di TK Nusa Indah Bulutengger Sekaran Lamongan: PENGARUH PENGGUNAAN MEDIA BALOK CUISENAIRE TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA DINI KELOMPOK B DI TK NUSA INDAH BULUTENGGER SEKARAN LAMONGAN - Astuti, Retno Dwi (Ali Muchasan, 2018)
This research which conducted at B group young learners of Nusa Indah kindergarten Bulutengger Sekaran Lamongan by using Cuisenaire rectangle aims to analyze the young learner’s counting skill to state the numeric symbol 1-10, matching the number and the symbol, and stating the result of the addition and abstraction from the thimgs correctly. The method of this research uses pre-eksperimental research by using quantitative approach and one-group pre-test design. The data analysis which uses Wilcoxon test shows that there is a difference between pre-test (before treatment)548, and post-test (after treatment) 770. The Tcount < Ttable (0<68). This research proves that there is an effect of using Cuisenaire rectangle for the B group children’s counting skill at Nusa Indah kindergarten Bulutengger Sekaran Lamongan.